Effect of V-Shaped Side Groove on Shear Lip Formation of Aluminium Alloy 6061 by Charpy Impact Test using Finite Element Analysis - Muhammad Syafiq Suresh, Muhammad Syabil; harimon, mohd azhar (Research Progress in Mechanical and Manufacturing Engineering, 2022)
In the automotive industry, aluminium alloy has been widely used for its own qualities which suits the industry. This study is to investigate the fracture properties of aluminium alloy 6061 with the presence of v-shaped side groove which is rarely investigated. Side groove can be characterised as a deep line cut on a specimen surface which is believed can reduce ductile behaviour during impact on the material. Ductile behaviour during impact is crucial as ductile behaviour undergoes plastic deformation before crack compared to brittle behaviour. The major goal of this research is to identify whether will side groove influences the fracture behaviour of AL-6061 as shear lip formation will be observed as the main objective of this research. A simulation of Charpy impact test with various side groove depths was conducted utilising ABAQUS 6.18 to identify the shear lips ratio, the absorb energy of the specimen and the displacement of the fracture. 3 different variation of side groove depths of 0.5, 1.5 and 2.5 mm has been used as the variable of this research. y. Based on the research, the shear lips ratio decreased when the side groove depths ratio increased. Besides, it was found that absorb energy decreased when the side groove depths ratio increased. In conclusion, increasing side groove depths ratio will tends to less ductility of Al6061 due to the less shear lips ratio and less absorb energy.